“Compassion”. The reception of Czesław Miłosz’s works in China - Zhao, Weiting (Transfer. Reception Studies, 2020)
The works of Czesław Miłosz have been translated into Chinese for about forty years. The turning point is marked by 1980, the year when the poet was awarded the Nobel Prize in Literature. The aim of the paper is to analyse the reception of Czesław Miłosz’s works by Chinese readers and to highlight the contexts associated with them. Until now, five vol-umes of the poet’s poetry have been published in China. In addition, five volumes of essays have been translated from Polish and one from English into Chinese. Reflecting the Chinese perception of Miłosz’s oeuvre, four stages of the reception history of his works can be traced. The presence and reception of the Polish Nobel Prize winner in Chinese culture is strongly influenced by the reception of all Eastern European literature in China. In addition to Chinese researchers of Polish and foreign literature, Miłosz’s works were also of interest to Chinese poets in the 1990s, who sought inspiration in his poetry to contem-porise their own poetry.